Effect to Goat Manure and Banana Hump POC on Growth and Yield of Pagoda Mustard (Brassica nanirosa L.) - A Miftakhurrohmat; Aulia Nahdhia Fitria (Nabatia, 2024)
The aim of the study was to determine the effect of growth and yield of Pagoda mustard greens (brassica nanirosa l.) on the administration of POC banana hump and goat manure, conducted in Ketimang Village, Wonoayu District, Sidoarjo Regency and follow-up observations were carried out at the Agrotechnology Laboratory of Muhammadiyah University of Sidoarjo from February to April. The study used a factorial randomized block design (RAK) with two factors and was repeated 3 times. The first factor is the dose of goat manure planting media consisting of 0ton/Ha, 20ton/Ha, and 40ton/Ha. The second factor was the dose of POC banana hump which consisted of 0ml/l water, 50ml/l water, and 100ml/l water. The variables observed were plant height, stem diameter, number of leaves, leaf area, wet weight, dry weight, and harvest index. The results showed that there was a significant interaction between goat manure at a dose of 40ton/ha and POC Bonggol Banana at a dose of 100ml/l water on the number of leaves at 35 DAP. Treatment of goat manure at a dose of 40ton/ha resulted in growth and yield production on plant height variables at the age of 42 DAP, 49 DAP, stem diameter, wet weight, and plant dry weight.